حسد اور نظر بد کے مضرات اور تدارک: قرآن وسنت کی روشنی میں تحقیقی مطالعہ: Remedies for the dangers of jealousy and evil eye: A research study in the light of Quran and Sunnah - Dr Hafsa Nasreen (Al Manhal Research Journal, 2024)
This paper deals with the effects of a very dangerous ailment i.e. jealousy. Jealousy (hasad) is not only harmful for others but for jealous (hasid) also. It is deeply connected with evil-eye. Jealous and those who give evil-eye are similar in that they both turn and adjust themselves to the one they wish to harm and destroy. They both inflict their harm upon others, whether they are present or not. Jealousy stems from hatred and enmity. The one who has enmity does not want the person he hates to be blessed by Allah rather he wants the opposite for him. Jealousy turns into evil eye which can kill a person in the light of Hadith. So it is necessary for the jealous (hasid) to know that one is not only harming others but is ruining one’s peace of mind and akhira. Besides this, everyone should seek Allah’s refuge from Hasid and ‘Ayin and manage to avoid hasidin.